2015
DOI: 10.1111/cmi.12404
|View full text |Cite
|
Sign up to set email alerts
|

Shedding light on host niches: label-freein situdetection ofMycobacterium gordonaevia carotenoids in macrophages by Raman microspectroscopy

Abstract: SummaryMacrophages are the primary habitat of pathogenic mycobacteria during infections. Current research about the host-pathogen interaction on the cellular level is still going on. The present study proves the potential of Raman microspectroscopy as a label-free and non-invasive method to investigate intracellular mycobacteria in situ. Therefore, macrophages were infected with Mycobacterium gordonae, a mycobacterium known to cause inflammation linked to intracellular survival in macrophages. Here, we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Several studies using laboratory strains demonstrated the successful detection and identification of medically relevant bacteria using Raman spectroscopy in combination with statistical data analysis . Based on the Raman spectral fingerprint, the discrimination of various pathogens and even between closely related strains was achieved, including S. aureus , S. epidermidis ,pathogenic and non‐pathogenic E. coli , Salmonella , Pseudomonas , Chlamydia , Enterococcus strains, mycobacteria, L. monocytogenes , and many more. Also, viral pathogens were objects of investigation in a clinical context, as it was reported for rotavirus, cytomegalovirus, influenza strains, human papillomavirus (HPV), Varicella zoster virus, and Porcine teschovirus , as well as echovirus 1 .…”
Section: Raman Spectroscopy For Medical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies using laboratory strains demonstrated the successful detection and identification of medically relevant bacteria using Raman spectroscopy in combination with statistical data analysis . Based on the Raman spectral fingerprint, the discrimination of various pathogens and even between closely related strains was achieved, including S. aureus , S. epidermidis ,pathogenic and non‐pathogenic E. coli , Salmonella , Pseudomonas , Chlamydia , Enterococcus strains, mycobacteria, L. monocytogenes , and many more. Also, viral pathogens were objects of investigation in a clinical context, as it was reported for rotavirus, cytomegalovirus, influenza strains, human papillomavirus (HPV), Varicella zoster virus, and Porcine teschovirus , as well as echovirus 1 .…”
Section: Raman Spectroscopy For Medical Applicationsmentioning
confidence: 99%
“…Intracellular accumulated bacteria possessed different molecular information than extracellular ones. Also, here, fluorescence imaging was used as a reference method to verify the Raman results . Raman microspectroscopy could also contribute to the investigation of intracellular and extracellular metabolic activity of Protochlamydia amoebophila , a model organism for symbiotic chlamydiae and the only non‐pathogenic chlamydia for which a genome sequence is available .…”
Section: Raman Spectroscopy For Medical Applicationsmentioning
confidence: 99%
“…By reducing spectral acquisition times to milliseconds, resonance Raman spectroscopy – a method in which the excitation wavelength matches the electronic transition of a selected molecule – was key to enabling the rapid imaging of these samples. It is also possible to visualize selected strains and their locations within habitats including human endothelial cells (Große et al, 2015), macrophages (Silge et al, 2015) and other environments, even when the taxa of interest are present at low abundances (Kalasinsky et al, 2007). Through combining imaging of Staphylococcus aureus cells with a multivariate classification model [based on principal component analysis (PCA) and linear discriminant analysis (LDA)], Große et al (2015) were further able to detect small differences in the spectral profiles that allowed the authors to discern between intra- and extracellular cells, due to shifts in the physiological state of the bacteria that occur upon host invasion.…”
Section: Raman Imagingmentioning
confidence: 99%
“…In order to apply an image-based technique to investigate the NM-cell interaction in situ, Raman microspectroscopy was the method of choice. The chemical information of a cell can be spatial resolved in the subcellular range to visualize the distribution of molecular composites [14][15][16][17][18][19][20][21]. The Raman-based analysis of cells is non-invasive, and no labeling technique is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The backscattered light of each map point is collected, dispersed on a grating, and detected by a CCD [20]. The resulting dataset of single Raman spectra is analyzed by chemometrical methods and combined with the spatial information to reconstruct the chemical landscape of the cell [15,17,18,20,21].…”
Section: Introductionmentioning
confidence: 99%